2016
DOI: 10.1186/s12885-016-2946-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of a randomized controlled trial of Internet-based cognitive behavioral therapy for treatment-induced menopausal symptoms in breast cancer survivors

Abstract: BackgroundMenopausal symptoms are common and may be particularly severe in younger women who undergo treatment-induced menopause. Medications to reduce menopausal symptoms are either contra-indicated or have bothersome side effects. Previous studies have demonstrated that face-to-face cognitive behavioral therapy (CBT) is effective in alleviating menopausal symptoms in women with breast cancer. However, compliance with face-to-face CBT programs can be problematic. A promising approach is to use the Internet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
(94 reference statements)
2
9
0
Order By: Relevance
“…Our findings showed that CBT is an effective treatment for QOL and psychological health of breast cancer survivors and patients. Recently, other delivery formats (eg, telephone‐delivered and internet‐based) have been shown to be equally effective and have the potential to significantly increase access to CBT . But this conclusion requires further research before such treatments can be applied to have comparable long‐term reliability and availability.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our findings showed that CBT is an effective treatment for QOL and psychological health of breast cancer survivors and patients. Recently, other delivery formats (eg, telephone‐delivered and internet‐based) have been shown to be equally effective and have the potential to significantly increase access to CBT . But this conclusion requires further research before such treatments can be applied to have comparable long‐term reliability and availability.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, other delivery formats (eg, telephone-delivered and internet-based) have been shown to be equally effective and have the potential to significantly increase access to CBT. 33 But this conclusion requires further research before such treatments can be applied to have comparable long-term reliability and availability. Cognitive behavior therapy showed more effect in depression of breast cancer patients in America than in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that cognitive-behavioral training has been effective in marital intimacy and identifying basic psychological needs among couples. These results are in line with the findings of Mohaddassi et al [19], Karimi and Khalatbari [21], Bagheri and Samsam Shariat [22], Ehsan Nejad et al [25], Pourmusa et al [27], and Hummel et al [18].…”
Section: Discussionsupporting
confidence: 92%
“…Also, previous results show that cognitive-behavioral therapy had a significant impact on the intimacy and marital satisfaction of betrayed women [19] and has a significant effect on increasing marital satisfaction, especially in improving communication and marital conflict, marital burnout resolution skills of couples, and their sexual relationships [23,24]. Also, this approach is effective in enhancing marital satisfaction and sexual satisfaction in postmenopausal women [25] and is effective in improving women's quality of life and happiness [26,27].…”
Section: Introductionmentioning
confidence: 90%
“…Clinicians should be aware of potential drug interactions with anticancer and adjuvant therapies (eg, see refs 21 22). Cognitive behavioral therapy may also improve menopause symptoms 23. For problems related to vulvovaginal atrophy, a variety of lubricants and bioadhesive moisturizers are available.…”
Section: Introductionmentioning
confidence: 99%